2019
DOI: 10.1093/gbe/evz149
|View full text |Cite
|
Sign up to set email alerts
|

Genome Resequencing Reveals Congenital Causes of Embryo and Nestling Death in Crested Ibis (Nipponia nippon)

Abstract: The crested ibis (Nipponia nippon) is endangered worldwide. Although a series of conservation measures have markedly increased the population size and distribution area of these birds, the high mortality of embryos and nestlings considerably decreases the survival potential of this bird species. High-throughput sequencing technology was utilized to compare whole genomes between ten samples from dead crested ibises (including six dead embryos and four dead nestlings aged 0–45 days) and 32 samples from living bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Schilling et al [47] found that at the final stage of hatching, embryos have immunity and can mount innate and adaptive immune responses to pathogens. Fu et al [48] found that the crested ibis (Nipponia nippon), an endangered bird worldwide, has a very high embryonic and nestling mortality rate, and comparing living and dead samples using high-throughput sequencing revealed that genes for glycan biosynthesis and metabolism (HYAL1 and HYAL4), as well as the immune system (JAM2), are associated with embryonic and nestling development. Serum immunoglobulins, especially IgA, IgG, and IgM produced by B cells, are important parameters reflecting the humoral immune status of animals and are associated with their important role in immune function and resistance to infection [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Schilling et al [47] found that at the final stage of hatching, embryos have immunity and can mount innate and adaptive immune responses to pathogens. Fu et al [48] found that the crested ibis (Nipponia nippon), an endangered bird worldwide, has a very high embryonic and nestling mortality rate, and comparing living and dead samples using high-throughput sequencing revealed that genes for glycan biosynthesis and metabolism (HYAL1 and HYAL4), as well as the immune system (JAM2), are associated with embryonic and nestling development. Serum immunoglobulins, especially IgA, IgG, and IgM produced by B cells, are important parameters reflecting the humoral immune status of animals and are associated with their important role in immune function and resistance to infection [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of population structure, relatedness, and levels of inbreeding can inform breeding decisions and provide crucial insight into the future viability of endangered populations ( Allendorf et al 2010 ). It is therefore important to evaluate the performance of different marker-based measures of inbreeding and understand how they relate to fitness-associated traits such as offspring survival ( Keller 1998 ; Fu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, levels of inbreeding were compared between the descendants of the mainland and Stewart Island founding populations to further investigate the impacts of previous bottlenecks ( Dussex et al 2018 ). Finally, we compared inbreeding estimates between deceased and surviving kākāpō chicks from a recent breeding season to understand potential genetic factors underlying premature mortality ( Fu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%